A Study on IP Network Recovery through Routing Protocols - K. Karthik; T. Gunasekhar; D. Meenu; M. Anusha (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Internet has taken major role in our communication infrastructure. Such that requirement of internet availability and reliability has increasing accordingly. The major network failure reasons are failure of node and failure of link among the nodes. This can reduce the performance of major applications in an IP networks. The network recovery should be fast enough so that service interruption of link or node failure. The new path taken by the diverted traffic can be computed either at the time of failures or before failures. These mechanisms are known as Reactive and Proactive protocols respectively. In this paper, we surveyed reactive and proactive protocols mechanisms for IP network recovery.